Lorazepam vs Diazepam for Status Epilepticus - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at the Division of Emergency Medicine, Children's National Medical Center, Washington, DC, and ten additional US centers in the Pediatric Emergency Care Applied Research Network (PECARN), conducted a double-blind, randomized clinical trial comparing the efficacy and safety of lorazepam and diazepam in the treatment of generalized convulsive status epilepticus (SE) in children aged 3 months to younger than 18 years.